Lower extremity dexterity is associated with agility in adolescent soccer athletes - Lyle, M. A.; Valero-Cuevas, F. J.; Gregor, R. J.; Powers, C. M. (Scandinavian Journal of Medicine & Science in Sports, 2015)
Agility is important for sport performance and potentially injury risk; however, factors affecting this motor skill remain unclear. Here, we evaluated the extent to which lower extremity dexterity (LED) and muscle performance were associated with agility. Fourteen male and 14 female soccer athletes participated. Agility was evaluated using a hopping sequence separately with both limbs and with the dominant limb only. The LED test evaluated the athletes` ability to dynamically regulate foot-ground interactions by compressing a spring prone to buckling with the lower limb. Muscle performance included hip and knee isometric strength and vertical jump height. Correlation analyses were used to assess the associations between muscle performance, LED, and agility. Multiple regression models were used to determine whether linear associations differed between sexes. On average, the female athletes took longer to complete the agility tasks than the male athletes. This difference could not be explained by muscle performance. Conversely, LED was found to be the primary determinant of agility (double limb: R2 = 0.61, P?<?0.001; single limb: R2 = 0.63, P < 0.001). Our findings suggest that the sensorimotor ability to dynamically regulate foot-ground interactions as assessed by the LED test is predictive of agility in soccer athletes. We propose that LED may have implications for sport performance, injury risk, and rehabilitation.